INFORMATION CULTURE OF TEACHER IN THE SYSTEM OF RELIGIOUS EDUCATION - Lomachinska, Irina; Lomachinskyi, Bohdan (Educological discourse, 2020)
The article deals with analysis of special aspects characterizing development of teacher’s information culture in the system of theological education that is based on principles of freedom of religion, non-confessionalism, and belief pluralism. Research methodology stipulates application of dialectical, comparative, structural, and functional research methods. The articles affirms that in the theological system of knowledge the phenomenon of information culture should be studied in view of the systems-based approach according to which society is an integral interaction system of social institutes – economic, political, social, faith-based institutions that guarantees its self-development basing on gained social and cultural experience. The information culture is a dynamic phenomenon that shows a relevant level of intellectual, educational, spiritual development of the society, and predetermines open-minded study of religion as a vital need to build the democratic society under conditions of active development of the globalized multicultural world. The article states that that issue of religion study is caused to a large extent by discussion of its essence that is affected by historical, confessional, political, legal factors, and existing educational practices. The research has established advantages of non-confessional, secular non-biased study of religion in historical, religious, ethical, and philosophic dimensions as lack of adequate knowledge of nature of religious processes in the secular society can have adverse effects not only for development of democratic social values but for preservation of collective memory of the nation. Findings of the research stress that in the theological educational discourse the information culture is realized in the system of measures aimed at improvement of informational self-awareness, formation of an informational world view based on tolerance, promotion of national information resources of national religious and social heritage, implementation of efficient scientific communication for the purposes of non-biased objective explanation of cause-and-effect links in the modern religious and political processes.